2001
DOI: 10.1063/1.1402162
|View full text |Cite
|
Sign up to set email alerts
|

Trends in bonding configuration at SiC/III–V semiconductor interfaces

Abstract: The structural and electronic properties of interfaces between β-SiC and III-V semiconductors are studied by first-principles calculations. Favorable bonding configurations are found to form between Si-V and C-III (model A) for BN, AlN, AlP, AlAs, GaN, GaP, GaAs, InN, InP, InAs and InSb, and Si-III and C-V (model B) for BP, BAs, BSb, AlSb and GaSb. The relationship between formation energy difference and lattice constant difference as well as charge distribution for these two models is found. The origin of bon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…From electrostatic arguments, cations (Si) favor bonding with anions (N) at the interface between III-N and SiC and visa versa. Therefore, the growth of the III (Ga, Al) polarity film on a Si polarity substrate is favorable [21][22][23]. This is in agreement with our results.…”
Section: Article In Presssupporting
confidence: 93%
See 3 more Smart Citations
“…From electrostatic arguments, cations (Si) favor bonding with anions (N) at the interface between III-N and SiC and visa versa. Therefore, the growth of the III (Ga, Al) polarity film on a Si polarity substrate is favorable [21][22][23]. This is in agreement with our results.…”
Section: Article In Presssupporting
confidence: 93%
“…Recently, theoretical and experimental studies indicated that the polarities of GaN and related III-N, GaN and thin AlN in this case, grown on SiC are affected by the polarity of SiC [21][22][23]. The bonding configuration, which is the origin of the polarity, is mainly explained in terms of the ionicity, electrostatic effect and charge distribution [22].…”
Section: Article In Pressmentioning
confidence: 98%
See 2 more Smart Citations
“…These results can be explained as follows. Previous studies on the interfaces between SiC and AlN have revealed favorable bonding configuration to be Si-N and C-Al rather than Si-Al and C-N. [38,39] Therefore, during the growth of SiC on AlN/ sapphire, a C-terminated surface is initially formed by the nature of the C-Al bonds, and then, Si atoms are subsequently adsorbed by a self-limiting process. That results in only an ideal Si-C-Al-N stacking sequence for the SiC growth.…”
Section: Resultsmentioning
confidence: 98%